2019
DOI: 10.1002/aoc.5060
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Decomposition Properties and Catalytic Mechanism of Ammonium Perchlorate over CuO/MoS2 Composite

Abstract: In this report, CuO/MoS2 composites were successfully prepared by the hydrothermal method where nano‐sized CuO was uniformly distributed on the surface of hierarchical MoS2 substrates (CuO/MoS2 composites). Their physicochemical properties and catalytic performance in ammonium perchlorate (AP) decomposition were investigated and characterized by XRD, SEM, TEM, BET, XPS, TG/DSC and combustion measurement. The results showed that it could decrease AP decomposition temperature at high decomposition stage from 416… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Hu et al. [ 350 ] proposed a generally hydrothermal method (see Figure a) for preparing CuO/MoS 2 composites. The obtained SEM and TEM in Figure 13b–d shows the wrinkles on the outer layer of MoS 2 structure and distribution of CuO nanoparticles on the surface of MoS 2 .…”
Section: Photoelectrochemical Properties Of Cuo Compositesmentioning
confidence: 99%
“…Hu et al. [ 350 ] proposed a generally hydrothermal method (see Figure a) for preparing CuO/MoS 2 composites. The obtained SEM and TEM in Figure 13b–d shows the wrinkles on the outer layer of MoS 2 structure and distribution of CuO nanoparticles on the surface of MoS 2 .…”
Section: Photoelectrochemical Properties Of Cuo Compositesmentioning
confidence: 99%
“…The O 1s spectra of the MoS 2 –NiO–CuO nanohybrid are shown in Fig S.1 . (a), four peaks for the O 1s are observed at 530.98, 531.81, 532.9, and 533.63 eV, which corresponds to the binding energies of MoO, O 1s, NiO, and CuO 37 , 38 . Finally, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The multielectron carrier could provide accelerated electrons and n-CuO could be receptive to the electrons of AP decomposition product ions and their intermediates, which might further enhance the efficiency of AP pyrolysis through synergistic effects. [19][20][21][22][23][24] For instance, graphene (G)/CuO composite exhibited high catalytic decomposition performance significantly reducing the HTD value of AP from 432 to 325 °C and decreasing the activation energy (E a ) by 57.53 kJ/mol. [25] It was shown that adding CuO/MoS 2 composites to AP could reduce the HTD value by 93 °C and enhance the whole heat release by 962 J/g.…”
Section: Introductionmentioning
confidence: 99%
“…[25] It was shown that adding CuO/MoS 2 composites to AP could reduce the HTD value by 93 °C and enhance the whole heat release by 962 J/g. [19] In addition, the maximum pyrolysis temperature of AP was reduced by 78.8 °C by adding 2 wt % MXene/CuO nanocomposite to the pure AP. [15] Theoretical studies showed that the pyrolysis process in AP was governed by two steps, including the electron transfer from ClO 4…”
Section: Introductionmentioning
confidence: 99%